2000
DOI: 10.2214/ajr.174.1.1740161
|View full text |Cite
|
Sign up to set email alerts
|

Inferiorly Displaced Flap Tears of the Medial Meniscus

Abstract: Inferior flap tears of the medial meniscus can be inconspicuous and overlooked by both radiologists and orthopedic surgeons. Inferiorly displaced meniscal fragments may escape detection during arthroscopic surgery unless the fragment is sought with a probing hook. Recognition of this meniscal abnormality on MR imaging is important for preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…In our series, the displaceable flap tears were found in 75 knees (75%) during arthroscopy. The clinical significance of a flap tear is that it can be displaced centrally or peripherally, leading to mechanical symptoms, which requires arthroscopic management19202122). Given that displaceable flap tears cause mechanical symptoms, it was hypothesized that 1) HCTs with a flap tear would be more symptomatic than HCTs without a flap tear, and 2) resultantly clinical outcomes after meniscectomy would be better in patients having combined flap tears compared to patients without flap tears.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the displaceable flap tears were found in 75 knees (75%) during arthroscopy. The clinical significance of a flap tear is that it can be displaced centrally or peripherally, leading to mechanical symptoms, which requires arthroscopic management19202122). Given that displaceable flap tears cause mechanical symptoms, it was hypothesized that 1) HCTs with a flap tear would be more symptomatic than HCTs without a flap tear, and 2) resultantly clinical outcomes after meniscectomy would be better in patients having combined flap tears compared to patients without flap tears.…”
Section: Discussionmentioning
confidence: 99%
“…Lecas et al .,[11] in a review of 3686 MRI examinations of the knee, reported 11 cases of torn meniscal fragments displaced inferiorly between the MCL and tibia. They also mentioned that semimembranosus tendon can be mistaken for such displaced meniscal fragments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extrusion of a part of the meniscus into the coronary recess below the joint line is seen on coronal as well as sagittal images. 38,49 These tears often present clinically with mechanical locking. It is important to identify the fragments before surgery, as the retention of meniscal flap often results in persistent pain and locking.…”
Section: Flap Tearmentioning
confidence: 99%